(untitled) (Research, Society and Development, 2023)
Cutting capacity and deformation of nickel-titanium files were compared in simulated phenolic resin channels with 75 degrees of curvature. Twenty blocks were dried and weighed on a digital analytical balance (P0), with group A preparing the canal with type K files associated with a Hedströen file and group B using type K files. After the first use, the blocks were dried and weighed again (P1) repeating the same procedure on the second (P2), third (P3), fourth (P4) and fifth (P5) uses. Before and after five readings performed microscopically at the tip of the instruments and 5 mm from the tip with 100X, 250X and 500X (SEM JEOL JSM-5900 LV/LME-LNLS – Laboratório Nacional de Luz Sínchrotron, Campinas, SP). Each micrograph evaluated by three teachers established a score. The results demonstrated that there was no statistical difference in relation to the cutting capacity of group A compared to group B (Pvalue>0.05), the same happening between the two evaluated points of the groups (Pvalue>0.05). When comparing the two groups considering the tip of the instrument and 5 mm from it, it was statistically significant (Pvalue<0.05), that is, the average score at the tip of the instrument is higher than that 5 mm from the tip. It was concluded that there was no difference in the removal of material after preparation of the canal in Group A in relation to group B. Deformation occurred in the cutting blades of the instruments, however, without statistical significance in the two points considered in the comparison of group A with B and the average deformations at the two points of the instruments were different the same groups.